How Jeff Smith built an Agile culture at IBM - Smith, Jeffrey (O'Reilly Media, Incorporated, 2018)
Since he was tapped as IBM's CIO in 2014, Jeff Smith has been playing a second key role: transforming IBM's internal software development culture to one that mirrors the Agile, user-centered, data-driven, and cross-functional approach that characterizes today's Silicon Valley startups. Except he's doing it for a team of 20,000 people, in support of a company with over 400,000 employees. We'll talk with Jeff about what it takes to get a hundred-year-old company to change course. This video clip comes from the 2016 Next:Economy Summit in San Francisco.